Lethal toxicity of monocrotophos on the juveniles of Anabas testudineus (Bloch) and Etroplus maculatus (Bloch) - Anna Mercy, T V; Kurup, B Madhusoodana; Nair, J R; Sulekha, B T (Indian Journal of Fisheries, 2011)
Studies on the lethal toxicity of the pesticide on two species of fish namely Anabastestudineus and Etroplus maculatus inhabiting the Kuttanad areas revealed thatthe 48 h LC50 values of monocrotophos on the juveniles of the respective fisheswere 102.59 and 3.36 ppm. Anabas was found to be more tolerant than Etroplus.Etroplus maculatus is a sensitive fish that can be used for toxicity monitoringin natural waters.